Pemahaman Masyarakat Tentang Bagi Hasil dan Bunga di Bank Syariah Indonesia - Tabroni, Muhammad; Rafidah, Rafidah; Alawiyah, Rabiyatul (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
From the perspective of its development, Islamic Banks are currently not lagging behind progress like conventional banks. Conventional Banking which applies an interest system runs side by side with Sharia Banking which applies a profit sharing system. The problem faced by Sharia Banks is the public's low knowledge about what systems exist in Sharia Banking. So people assume or are seen that Islamic Banks are the same as Conventional Banks. This research aims to analyze the public's understanding of profit sharing and interest in Indonesian Sharia Banks (case study of the community or religious leaders of the Sa'adatuddaren Islamic Boarding School in Tahtul Yemen). This research uses qualitative research methods. Data collection techniques using observation, interviews and documentation. The number of respondents in this study was 13 people. The results of this research are (1) Tahtul Yamanl community does not understand the profit sharing system in Sharia Banks, (2) Tahtul Yaman community thinks that the profit sharing and interest systems are both just for profit, (3) a small number, such as religious figures, understand about profit sharing in Sharia Banks Keywords: community, profit sharing, Sharia Banks